Age‐Dependent Levels of 5‐Methyl‐, 5‐Hydroxymethyl‐, and 5‐Formylcytosine in Human and Mouse Brain Tissues1. Issue 42 (3rd July 2015) - Wagner, Mirko; Steinbacher, Jessica; Kraus, Theo F. J.; Michalakis, Stylianos; Hackner, Benjamin; Pfaffeneder, Toni; Perera, Arshan; Müller, Markus; Giese, Armin; Kretzschmar, Hans A.; Carell, Thomas
Abstract The absolute levels of 5‐hydroxymethylcytosine (hmC) and 5‐methylcytosine (mC) in human brain tissues at various ages were determined. Additionally, absolute levels of 5‐formylcytosine (fC) in adult individuals and cytosine modification levels in sorted neurons were quantified. These data were compared with age‐related fC, hmC, and mC levels in mouse brain samples. For hmC, an initial steady increase is observed, which levels off with age to a final steady‐state value of 1.2 % in human brain tissue. This level is nearly twice as high as in mouse cerebral cortex. In contrast, fC declines rapidly with age during early developmental stages, thus suggesting that while hmC is a stable epigenetic mark, fC is more likely an intermediate of active DNA demethylation during early brain development. The trends in global cytosine modification dynamics during the lifespan of an organism are conserved between humans and mice and show similar patterns in different organs.